Implementasi Good Governance dalam Pelayanan Publik di Kantor Desa Penataran - Sintia Wahyu Pratiwi; Ferida Asih Wilujeng; Jalu Sora Wicitra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe the implementation of good governance principles in public services at the Penataran Village Office, Nglegok District, Blitar Regency. The research uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The results show that good governance principles such as transparency, accountability, participation, effectiveness, efficiency, and the rule of law have been well implemented at the village office. However, there are some obstacles in the implementation, such as limited technology, unequal participation, and administrative constraints that affect public service performance. To overcome these challenges, the village government conducts training for village officials, utilizes conventional media to improve communication with the community, and strengthens coordination and mediation between stakeholders. The findings highlight the importance of an adaptive and collaborative approach in building responsive village governance that is oriented toward the needs of the community. Thus, the application of good governance principles in Penataran Village is expected to improve the quality of public services and encourage the realization of a better and more transparent government.